2018
DOI: 10.3390/f9050253
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Biomass and Woody Litter for Bio-Energy in Biscay (Spain)

Abstract: Forest management has been considered a subject of interest, because they act as carbon (C) sinks to mitigate CO 2 emissions and also as producers of woody litter (WL) for bio-energy. Overall, a sustainably managed system of forests and forest products contributes to carbon mitigation in a positive, stable way. With increasing demand for sustainable production, the need to effectively utilise site-based resources increases. The utilization of WL for bio-energy can help meet the need for renewable energy produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Former studies have shown that thinning intensification significantly increases the quantity of total biomass obtained (timber and residue biomass). However, this type of management can reduce carbon sequestration in forests [4]. For this reason, in this research an average forest management which optimizes economic (quantity of timber biomass) and environmental (CO2 sequestration) factors has been assumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former studies have shown that thinning intensification significantly increases the quantity of total biomass obtained (timber and residue biomass). However, this type of management can reduce carbon sequestration in forests [4]. For this reason, in this research an average forest management which optimizes economic (quantity of timber biomass) and environmental (CO2 sequestration) factors has been assumed.…”
Section: Discussionmentioning
confidence: 99%
“…This province is situated on the banks of the Cantabria Sea, in the north of the Iberian Peninsula. Site characteristics were detailed in a previous paper [4]. It is a mountainous province with slopes often exceeding 30%.…”
Section: Study Areamentioning
confidence: 99%
“…A previous study investigated the biomass production of predominant forest species Pinus radiata D. Don and Ecualyptus globulus Labill of Biscay using data from the Spanish Forest Inventories and reported that the Forests of Biscay stored 12.084 teragrams of biomass of dry basis in 2005 and 14.509 terahrams of biomass of dry basis in 2011 [14]. Although, the forest is a renewable resource, its accounting and management is vital for sustainability.…”
Section: Introductionmentioning
confidence: 99%